Working in partnership to strengthen health librarianship – Shane Godbolt's legacy. (16th December 2020) - Farrow, Emma; Cotera Zubeldia, Maria
Abstract: This paper focuses on Shane Godbolt's commitment to international librarianship and global health and her guiding principles for international working. The authors examine and celebrate how these have been applied in practice, impacting many.